2019
DOI: 10.1289/ehp3556
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Urban–Rural Disparity in Temperature–Mortality Relationships in Zhejiang Province, China

Abstract: Background:Temperature-related mortality risks have mostly been studied in urban areas, with limited evidence for urban–rural differences in the temperature impacts on health outcomes.Objectives:We investigated whether temperature–mortality relationships vary between urban and rural counties in China.Methods:We collected daily data on 1 km gridded temperature and mortality in 89 counties of Zhejiang Province, China, for 2009 and 2015. We first performed a two-stage analysis to estimate the temperature effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 64 publications
7
58
1
Order By: Relevance
“…Several studies have reported that socioeconomic factors independently affected the association of temperature with mortality counts [5,9,10]. For instance, several studies reported that temperaturemortality relationships had difference between urban and rural areas [11][12][13], gross domestic product (GDP) and average educational years also could explain spatial heterogeneity of temperature-related effects [10,14,15]. Based on these, we hypothesize that low socioeconomic development regions (LDRs) maybe more vulnerable to ambient temperature than high development regions (HDRs), which has not been examined in the previous studies at national level.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that socioeconomic factors independently affected the association of temperature with mortality counts [5,9,10]. For instance, several studies reported that temperaturemortality relationships had difference between urban and rural areas [11][12][13], gross domestic product (GDP) and average educational years also could explain spatial heterogeneity of temperature-related effects [10,14,15]. Based on these, we hypothesize that low socioeconomic development regions (LDRs) maybe more vulnerable to ambient temperature than high development regions (HDRs), which has not been examined in the previous studies at national level.…”
Section: Introductionmentioning
confidence: 99%
“…However, exposure risk assessment requires consideration of all microenvironments where humans spend most of the time [12]. The weather-related mortality associations in a city using exposure variables from one local weather station or the average from a network of sites could induces exposure measurement error or biases in the estimates [13]. More recently, satellite-measured land surface temperature (LST) has been used to identify the temperature variations at a high spatial resolution [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, LST cannot serve as a proper proxy for the daily mean temperature mainly due to their sparse temporal coverage (one measurement per day) [15]. Numerous studies have spatially interpolated temperature data from multiple measurement sites, but this is often limited by the sparse distribution of weather stations that cannot accurately measure temperature variations within a study area [13].…”
Section: Introductionmentioning
confidence: 99%
“…More localized features of heat stroke casualties have been investigated for many parts of the world with respect to urban-rural difference (Tan et al 2010;Gabriel and Endlicher 2011;Li et al 2017;Hu et al 2019) and intra-city variations (Vaneckova et al 2010;Chan et al 2012;Hondula et al 2012;Harlan et al 2013;Rosenthal et al 2014;Madrigano et al 2015;Kim and Kim 2017;Schinasi et al 2018), although these studies target "heatrelated mortality" defined by excessive mortality under high temperature rather than heat-stroke deaths in a nar- row sense. While some of them paid attention to both climatic and social factors, such as economic state and education, the results are not sufficiently consistent to provide a unified view of the spatial variation of heatrelated mortality.…”
Section: Introductionmentioning
confidence: 99%